Privatization of Railways: A Bibliometric and Systematic‎Analysis of Global Research Trends - Gupta , Ashok Kumar; Indapurkar , Dr. Kavita (International Journal of Accounting and Economics Studies, 2025)
This study offers a comprehensive bibliometric and systematic review of global research on railway privatization spanning from 1991 to ‎‎2025. Utilizing a dual-method approach, the analysis draws on 632 peer-reviewed articles retrieved from the Scopus database. The bibliometric component maps publication trends, influential authors, leading institutions, and thematic clusters using tools such as VOSviewer ‎and Biblioshiny. The systematic review complements this with critical insights into research themes, policy frameworks, and methodological ‎developments. The study identifies key geographic contributors—including the United Kingdom, China, India, Japan, and Sweden—and ‎reveals four dominant thematic clusters: economic efficiency and deregulation, governance in public-private partnerships (PPPs), sustainability and urban transport, and high-speed rail reforms. Despite a robust focus on operational efficiency, risk management, and investment ‎models, the review highlights major thematic gaps. Issues like labor rights, equity, environmental sustainability, and representation of the ‎Global South remain underexplored. Co-citation and keyword analyses reveal a technocratic bias, often sidelining the socio-political and ‎environmental dimensions of privatization. The study concludes that while railway privatization research has matured in volume and sophistication, its relevance and inclusiveness can be enhanced by integrating interdisciplinary methods, expanding regional diversity, and embed-‎ding social justice into governance discourse. Future research must address these imbalances to support equitable, sustainable, and resilient ‎railway systems globally‎.